Visible light communication: implementation and analysis - V. Bhalerao, M.; Sumathi, M.; S. Sonavane, S. (International Journal of Engineering and Technology, 2018)
Major research in Visible Light Communication is at simulation level and researcher needs a test system for the physical implementation of VLC. LEDs are predominantly used everywhere due to greater development in technology of light sources. LED sources are used in Visible Light Communication for an eco-friendly world due to its advantages over conventional wireless communication systems like Radio Frequency. Communication between two personal computers using Visible Light Communication system is implemented and tested for various distances between transmitter and receiver. The neutral white LED array of 12W and PIN photodiode for visible light range is used for downlink purpose and uplink is implemented using simple IR LED and photodiode. The system is implemented using ATmega328 board. Maximum communication distance is achieved up to 2.1 m.